Fenomena Berkurangnya Misleading Advertising pada Iklan Baris di Surat Kabar (Penegakan Etika Periklanan untuk Perlindungan Konsumen): (Penegakan Etika Periklanan untuk Perlindungan Konsumen) - Muhammad Khoiruman; Ambar Wariati (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2021)
Classified ads in newspapers are a form of advertisement widely used by small businesses or individuals who offer goods and services. This study aims to describe and explain the phenomenon of classified advertisements that often occur in newspapers, especially local newspapers, and to identify how far classified advertisements in newspapers follow advertising ethics and legislation so that readers as advertising objects are not misled by the information contained in the advertisements. This type of research is normative-empirical, which uses a qualitative approach. The research examines legislation, regulations that discuss advertising and consumer protection and empirically dig up information in the field about classified ad impressions in newspapers that are considered misleading advertising, and makes observations and digs up information to competent parties with the problem under study. The results showed that some classified advertisements in local newspapers with limited information made the advertisements misleading advertising. Still, there was the fact that there was a significant decrease in the number of classified ads in local newspapers as well as a reduction in the number of misleading advertising that was caused. This phenomenon is caused by 1) the number of classified advertisements as a whole has decreased drastically 2) The awareness of newspaper editors regarding consumer protection for advertisement readers in newspapers has begun to be implemented by accommodating Indonesian Pariwara Ethics, Law No: 8/1999 on Consumer Protection, Law No: 40/1999 concerning PRESS, Law No: 7 1996 concerning Food, and PP No.69 concerning Food Label and Advertising. 3) Much online advertising space, both paid and free, is also the cause of the reduction in misleading advertisements in newspapers today.